2019
DOI: 10.1039/c9ta08848b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bromide content on iodide migration in inverted MAPb(I1−xBrx)3perovskite solar cells

Abstract: Impedance spectroscopy shows the bromide concentration required to supress the low frequency response from mobile ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 76 publications
7
59
0
Order By: Relevance
“…Figure 11 illustrates the Nyquist plots for devices fabricated using NiO x and 5% Zn-NiO x thin films annealed at 250 • C. EIS measurement was taken at one solar illumination using a frequency range from 10 Hz to 1 MHz with an AC amplitude of 0.01 V, and providing a bias voltage that matched the open-circuit voltage. The impedance curve was observed at three frequency regions where the high-frequency (HF) regime correlates with charge transport resistance (Rct) at the HTL/perovskite interface, mid-frequency (MF) region is related to charge recombination, and low-frequency (LF) has been associated to iodide ion modulated recombination/injection process [47]. The curves were fitted with the equivalent circuit and the calculated Rct values are~60.38 Ω and 45.62 Ω for NiO x and 5% Zn-NiO x devices, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 11 illustrates the Nyquist plots for devices fabricated using NiO x and 5% Zn-NiO x thin films annealed at 250 • C. EIS measurement was taken at one solar illumination using a frequency range from 10 Hz to 1 MHz with an AC amplitude of 0.01 V, and providing a bias voltage that matched the open-circuit voltage. The impedance curve was observed at three frequency regions where the high-frequency (HF) regime correlates with charge transport resistance (Rct) at the HTL/perovskite interface, mid-frequency (MF) region is related to charge recombination, and low-frequency (LF) has been associated to iodide ion modulated recombination/injection process [47]. The curves were fitted with the equivalent circuit and the calculated Rct values are~60.38 Ω and 45.62 Ω for NiO x and 5% Zn-NiO x devices, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…So far there have only been a limited number of studies focusing on these regimes, using AC impedance spectroscopy or DC polarization measurements. 15 , 16 Although these works shed light on ion migration in mixed-halide perovskites, the full picture remains elusive, specifically whether the trends observed stem from iodide or bromide migration, and how to attribute the relative contributions to the ion migration process, in terms of migration activation energy, ion diffusion coefficient, and concentration of mobile ions.…”
Section: Introductionmentioning
confidence: 99%
“…Critically, the study highlights that the LPK blocks the escape of MAI, making the degradation process reversible, further affirming that LPKs suppress both vacancy migration, as well as, interfacial ion migration. [119][120][121] In devices, the introduction of an LPK layer between the 3D material and the hole transporting material (HTM) has been shown to improve device stability and reduce hysteresis. [115,[123][124][125] For instance, Grancini et al showed that the aminovaleric acid (AVA) based perovskite (AVA) 2 PbI 4 /CH 3 NH 3 PbI 3 ) is stable for one year.…”
Section: Enhancing Stability With Layered Structuresmentioning
confidence: 99%